Factors associated with virologic failure among patients receiving antiretroviral therapy in Butha -Buthe district, Lesotho - Maile, Khotso (My University, 2019)
Background A substantial number of patients in Lesotho fail to achieve viral load suppression. However, evidence on the predictors of viral load non – suppression is still scarce in the country. This study aims to determine predictors of virologic failure among patients receiving antiretroviral therapy in Butha – Buthe district 12 months after the introduction of routine viral load (VL) monitoring. Methods: The study was based on secondary data analysis of an on-going dynamic cohort of 4448 Butha – Buthe ART patients receiving VL monitoring during December 2015 to November 2016. Patients were selected for participation if they had been on ART for six or more months and had at least one viral load measurement. Medians (inter-quartile range (IQR)) and frequency tables were used to describe continuous and categorical variables respectively. Stepwise model building technique was used to develop the multivariable logistic regression model which was used for determining factors associated with virologic failure (≥1000copies/ml). Results: Of 4448 patients who participated in the study, the median age 43 years (IQR 35 – 53) and patients were predominantly females, 3073 (69.1%). The prevalence of virologic failure was 7.4%. In multivariable analysis, being on alternative 1st line ART regimen [(AZT + 3TC + EFV) or (ABC + 3TC + EFV)] [(Adjusted Odds Ratio (AOR) 3.67, 95% CI 2.16, 6.25; p<0.001)] increased the odds of virologic failure compared to being on the preferred 1st line (TDF + 3TC + EFV). Similarly, patients who were virologically monitored because they were being targeted for immunological failure (AOR 8.25, 95% CI 1.08, 63.05; p=0.042) and for clinical failure (AOR 9.53, 95% CI 2.79, 32.57; p<0.001) had increased odds of virologic failure compared to routine viral load testers. Missing a single or more doses of ART in past 30 days (OR 2.91, 95% CI 1.45, 5.83; p=0.003) significantly increased the odds virologic failure compared to adhering well. But, being a breastfeeding mother (AOR 1.45, 95% CI 0.83, 2.53; p=0.187) was not associated with virologic failure. Conclusion: The study results identified some of the predictors of virologic failure in and groups at increased risk of virologic failure in Lesotho. Targeted interventions such as enhanced adherence counselling are recommended for these failure groups.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree Master of Science in Epidemiology in the Field of Epidemiology and Biostatistics October 2019